Managing Lakes and Lake Basins for Sustainable Use - World Bank (Washington, DC, 2012)
Lakes and reservoirs are the world's major repository of accessible freshwater. They are central to the livelihoods and economies of a large fraction of the world's population, as well as being centers of aquatic biodiversity. They play a central role in integrated water resources management. Yet in spite of their importance and the growing threats to them, they have not received sufficient attention in the global discussion on water policy. The Lake Basin Management Initiative (LBMI) was implemented as a cooperative program supported by a partnership of many international agencies to draw on global knowledge on Lake Basin management. An analysis of experiences from 28 lakes around the world sought to identify practical lessons learned from management of lake basins, create new knowledge on Lake Basin management, fill an important gap in knowledge of lake management in developing countries, and derive lessons from internationally funded projects.